Cytochromes P450 Inhibitory Excipient-Based Self-Microemulsions for the Improved Bioavailability of Protopanaxatriol and Protopanaxadiol: Preparation and Evaluation - Yang, Feifei; Zhou, Jing; Liu, Chunyu; Hu, Xiao; Pan, Ruile; Chang, Qi; Liu, Xinmin; Liao, Yonghong (Planta Medica, 2017)
Protopanaxatriol and protopanaxadiol exhibit limited oral bioavailability due to the poor solubility and intestinal cytochromes P450-mediated metabolism. This study set out to develop a novel cytochromes P450 inhibitory excipient(s)-based self-microemulsion to encapsulate protopanaxatriol and protopanaxadiol so as to enhance the in vivo bioavailability by inhibiting intestinal metabolism. After screening the inhibitory effect of pharmaceutical excipients on the cytochromes P450-mediated metabolism, two self-microemulsions, SME-1 and SME-2, with similar physicochemical properties were prepared by using either active inhibitory excipients or corresponding inactive excipients. The results showed that no significant difference existed in the profiles of in vitro release, cellular uptake, and permeability in Caco-2 cells, and in vivo lymphatic transport between self-microemulsion-1 and self-microemulsion-2. The in vivo pharmacokinetic experiments indicated that self-microemulsion-1 conferred to significantly higher absolute bioavailability of protopanaxatriol (19.55 %) and protopanaxadiol (100.07 %) than those of the free drug (2.21 % and 23.70 %, respectively) or of self-microemulsion-2 (4.95 % and 45.35 %, respectively). The present work demonstrated that the presence of cytochromes P450 inhibitory excipients in self-microemulsion-1 tended to inhibit intestinal cytochromes P450-mediated metabolism and subsequently improved the oral bioavailability of protopanaxatriol and protopanaxadiol.
Keywords: protopanaxatriol (PPT); protopanaxadiol (PPD); self-microemulsion; CYP450; oral bioavailability